ANALISIS CAPITAL ASSET PRICING MODEL (CAPM) DALAM PENGAMBILAN KEPUTUSAN INVESTASI SAHAM (STUDI PADA SAHAM YANG LISTING DI JAKARTA ISLAMIC INDEX PERIODE 2015-2017) - Ditha Indah Fatmasari; R. Deni Muhammad Danial; Nor Norisanti (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2019)
This research aims to determine various stock investments with the Capital Asset Pricing Model(CAPM) method, to help investors pick efficient and inefficient stock. The population in thisstudy are all companies listing in Jakarta Islamic Index. The sampling technique used waspurposive sampling method and acquired 16 stocks. The results show that there was positiverelationship or non linear relationship between systematic risk and expected return. There are13 stocks included on efficient and investment decisions should be taken by investors was tobuy efficient stocks, while there are 3 stocks included on inefficient and investment decisionsshould be taken by investors was to sell inefficient stocks.Keywords: Capital Asset Pricing Model (CAPM), Systematic Risk, Investment Decisions